2018
DOI: 10.1088/1752-7163/aabf98
|View full text |Cite
|
Sign up to set email alerts
|

Online monitoring of carbon dioxide and oxygen in exhaled mouse breath via substrate-integrated hollow waveguide Fourier-transform infrared-luminescence spectroscopy

Abstract: Exhaled breath offers monitoring bio markers, as well as diagnosing diseases and therapeutic interventions. In addition, vital functions may be non-invasively monitored online. Animal models are frequently used in research for determining novel therapeutic approaches and/or for investigating biological pathways. The exhaled carbon dioxide concentration, exhaled and inhaled oxygen concentration, and the subsequent respiratory quotient (RQ) offer insight into metabolic activity. One may adapt breath sampling sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The sample volume was calculated as 315 μL, and the sensor was applied for an online monitoring of exhaled mouse breath performed in 14 mechanically ventilated and instrumented mice (Figure 12). Seichter et al 54 demonstrated the usage of a compact FTIR-iHWG-based gas sensor to monitor 12 CO 2 / 13 CO 2 and oxygen by a luminescence-based flow-through sensor integrated into the respiratory equipment of the mouse intensive care unit (MICU). These systems are nowadays in routine use in MICU stations and for the first time provide real-time information on the physiological condition of small animals via a noninvasive exhaled breath analysis.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The sample volume was calculated as 315 μL, and the sensor was applied for an online monitoring of exhaled mouse breath performed in 14 mechanically ventilated and instrumented mice (Figure 12). Seichter et al 54 demonstrated the usage of a compact FTIR-iHWG-based gas sensor to monitor 12 CO 2 / 13 CO 2 and oxygen by a luminescence-based flow-through sensor integrated into the respiratory equipment of the mouse intensive care unit (MICU). These systems are nowadays in routine use in MICU stations and for the first time provide real-time information on the physiological condition of small animals via a noninvasive exhaled breath analysis.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Therefore, multiple efforts have been undertaken to closer simulate the real world in trauma, burn and sepsis research [ 161 ] including international expert consensus initiatives to improve animal modelling [ 162 ] addressing among others the principle of “refinement”. Moreover, the use of a mouse- or pig intensive care unit seems to provide a higher degree of clinical simulation, validity and reliability [ 138 , 163 ]. Furthermore, the better definition of the inflicted injury on well-defined anatomical regions helps to standardize the injury pattern and thus provides a better if not superior comparison with specific human situations [ 164 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of 12 CO 2 , 13 CO 2 , and O 2 concentrations, as well as the respiratory quotient (RQ) in mouse breath, has already been enabled by our research team via various analytical tools (i.e., iHWG-FTIR spectroscopy, interband cascade laser based tunable diode laser absorption spectroscopy (TDLAS), and LS) [46,47,48]. Besides these already quantifiable analytes in mouse breath, the detection of additional volatile compounds such as acetone and H 2 S is desirable for therapy monitoring and to aid in understanding the underlying metabolism of traumatized mice.…”
Section: Introductionmentioning
confidence: 99%